Characterization of charcoals produced from Acacia, Albizia and Leucaena for application in ironmaking - Singh A.K.; Singh R.; Sinha O.P. (My University, 2025)
Fossil coal can be replaced with renewable charcoal to reduce CO2 emissions from ironmaking processes. Charcoals produced from three hardwood species, Acacia nilotica (W1), Albizia lebbeck (W2) and Leucaena leucocephala (W3), were evaluated as a reductant in ironmaking. Charcoals were produced with slow (5 °C/min) and fast heating rates (50 °C/min) at 600, 800 and 1100 °C. Charcoals were characterized using proximate, ultimate analysis, volume shrinkage, compressive loading, scanning electron microscopy, Fourier transform infrared spectroscopy and Raman spectroscopy for their chemical, mechanical and physical properties. It was found that among the selected biomass species, fixed and total carbon content is higher in W1 (83–97; 84–91%) and W2 (83–96; 86–92%) than W3 (76–89; 78–84%) and increases with increase in carbonization temperature and heating rate. Charcoal yield in W1 (22–28%), W2 (22–26%) and W3 (23–28%) decreases with an increase in carbonization temperature and heating rate. Charcoals produced at various carbonization conditions have at most 10% ash content. Values from different tests indicate that W2 and W3 charcoal are potentially better reductant than W1. © 2022 Elsevier Ltd